Toward a Framework for Indonesian Medical Question Generator - Wiwin Suwarningsih; Iping Supriana; Ayu Purwarianti (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
Question generating is the task of automatically generating questions from various inputs such as raw text, database, or semantic representation. In this paper, we attempt to describe a general framework that could help develop and characterize efforts to medical Indonesian generates questions medical text. We propose a new style of question generation that actively uses sentences within a document as a source of answer. We use manually written rules to perform a sequence of general purpose a syntactic transformation (e.g. identification of keywords or key phrase to NER based on PICO frame) to turn a declarative sentence into questions. The final result of this research is a pattern of question and answer pairs, where the test results show the pattern matching algorithm precision value of 0.101 and a recall of 0.712.